2014
DOI: 10.1080/10495398.2014.941468
|View full text |Cite
|
Sign up to set email alerts
|

MAC-T Cells as a Tool to Evaluate Lentiviral Vector Construction Targeting Recombinant Protein Expression in Milk

Abstract: Prior to generating transgenic animals for bioreactors, it is important to evaluate the vector constructed to avoid poor protein expression. Mammary epithelial cells cultured in vitro have been proposed as a model to reproduce the biology of the mammary gland. In the present work, three lentiviral vectors were constructed for the human growth hormone (GH), interleukin 2 (IL2), and granulocyte colony-stimulating factor 3 (CSF3) genes driven by the bovine β-casein promoter. The lentiviruses were used to transduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…The transduction and selection of bovine fibroblasts and MAC-T cells were performed as previously described. 14,24 The fibroblast cultures were performed using DMEM-high glucose medium (Gibco # 11995065, Carlsbad, CA), 10% fetal bovine serum (Gibco # 26140079, Carlsbad, CA), 100 units mL −1 penicillin (Sigma-Aldrich # P3032, St. The primers were the forward 5′-GGCGTGAACCACGAGAAGTATAA-3′ and reverse 5′-CCCTCCACGATGCCAAAGT-3′.…”
Section: Bovine Mac-t Cells and Fibroblast Transductionmentioning
confidence: 99%
“…The transduction and selection of bovine fibroblasts and MAC-T cells were performed as previously described. 14,24 The fibroblast cultures were performed using DMEM-high glucose medium (Gibco # 11995065, Carlsbad, CA), 10% fetal bovine serum (Gibco # 26140079, Carlsbad, CA), 100 units mL −1 penicillin (Sigma-Aldrich # P3032, St. The primers were the forward 5′-GGCGTGAACCACGAGAAGTATAA-3′ and reverse 5′-CCCTCCACGATGCCAAAGT-3′.…”
Section: Bovine Mac-t Cells and Fibroblast Transductionmentioning
confidence: 99%
“…16 In contrast to the plasmid vectors, there are no commercial lentiviral vectors available for expressing recombinant proteins in milk, although some authors have modified commercial lentiviral vectors for this purpose 17,18,19 (Fig. 1).…”
Section: Vectors Used In the Generation Of Transgenic Animalsmentioning
confidence: 99%
“…29 Others studies have used MEC cultures to evaluate the expression of the vectors constructed. 13,18,19,30 Although transgenic mice may be the best model for transgenic farm animals, MEC culture is a strategy that is easier to execute than the generation of transgenic mice and shows certain advantages, such as a lower cost and an elimination of the necessity for a vivarium to produce and house transgenic mice.…”
Section: Vectors Used In the Generation Of Transgenic Animalsmentioning
confidence: 99%
“…Therefore, we have adopted this vector to produce the lentiviruses and use them as a control to the standardization of zygote transduction. We have constructed other lentiviral vectors by directing the recombinant protein expression in the milk [10] and used the lentivirus to promote zygote transduction.The lentivirus was produced in 293-FT cells, and then concentrated concentrated about 100-fold using PEG, before the transduction. The analysis by q-PCR showed that the concentration of lentivirus from FUGW and the constructed vectors had similar quantities of lentiviral particles.…”
mentioning
confidence: 99%
“…Therefore, we have adopted this vector to produce the lentiviruses and use them as a control to the standardization of zygote transduction. We have constructed other lentiviral vectors by directing the recombinant protein expression in the milk [10] and used the lentivirus to promote zygote transduction.…”
mentioning
confidence: 99%